2020
DOI: 10.1080/19476337.2020.1715486
|View full text |Cite
|
Sign up to set email alerts
|

Variations in fatty acid composition and antioxidant content in olive fruits as a result of the application of phytoregulators to the olive tree (Olea europaeaL.)

Abstract: A new procedure to minimize the degradation of fatty acids and polyphenols during the olive storage is here proposed. This procedure is based on pre-harvest treatments of Arbequina and Picual olive trees with methyl jasmonate and abscisic acid. As a result, total phenolic content increased in all treated Arbequina olives as compared with controls. In contrast to Arbequina, only abscisic acid resulted in total phenolic content increase in Picual olives. Regarding the antioxidant activity, neither of the phytore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(30 reference statements)
2
1
0
Order By: Relevance
“…Since, during the current extraction ethanol was employed as extracting solvent; it might be a chance that relatively a higher content of C18 : 3 (11.37 %) has been extracted in to the extraction media as compared with linoleic acid (2.65 %) and while negligible amount of oleic acid is detected. In another study, C18 : 3 was found to be 2.54 % in Arbequina and 1.22 % in Picual olives [35] . In the present work, undecanoic acid ethyl ester is also detected in minor concentration.…”
Section: Phytochemicals Characterization In Gof Extract Using Gc/mssupporting
confidence: 68%
See 1 more Smart Citation
“…Since, during the current extraction ethanol was employed as extracting solvent; it might be a chance that relatively a higher content of C18 : 3 (11.37 %) has been extracted in to the extraction media as compared with linoleic acid (2.65 %) and while negligible amount of oleic acid is detected. In another study, C18 : 3 was found to be 2.54 % in Arbequina and 1.22 % in Picual olives [35] . In the present work, undecanoic acid ethyl ester is also detected in minor concentration.…”
Section: Phytochemicals Characterization In Gof Extract Using Gc/mssupporting
confidence: 68%
“…In another study, C18 : 3 was found to be 2.54 % in Arbequina and 1.22 % in Picual olives. [35] In the present work, undecanoic acid ethyl ester is also detected in minor concentration. The presence of ethyl ester may be linked to the fermentation/degradation of olives [36] and its formation may result during sample treatment and processing.…”
Section: Phytochemicals Characterization In Gof Extract Using Gc/mssupporting
confidence: 58%
“…In particular, high levels of cytokinins (CKs), gibberellins (GAs), and polyamines (PAs) have been reported in the developing olive fruits [5,70,71], whereas abscisic acid (ABA), salicylic acid (SA), and GAs are abundant in the ripe olive fruit [65]. In this context, the preharvest application of plant hormones to different olive cultivars has recently been reported to increase fruit size and to boost the content of bioactive components and antioxidants, among other components, and thus to preserve the oxidative stability of olive fruits during storage [72][73][74][75][76]. Recently, it has been demonstrated that CKs and SA correlate positively with cell division during early olive fruit development, while GA, auxin, and ABA have higher relative importance in the period when olive fruit growth depends mainly on cell expansion [20].…”
Section: Introductionmentioning
confidence: 99%